MENELAAH KOMPLEKSITAS KEBIJAKAN DALAM PENGATURAN KONFLIK KEPENTINGAN DAN TINDAK PIDANA KORUPSI: STUDI PERBANDINGAN INDONESIA DAN SINGAPURA - Pardede, Rudi (Smart Education, 2026)
Abstract: This study examines the complexity of policies governing conflicts of interest and corruption between Indonesia and Singapore through a normative juridical approach. The study was conducted by examining the regulatory framework, institutions, and legal implementation in preventing the practice of abuse of public office. The results of the study indicate that the Indonesian regulatory framework, although comprehensive, tends to function as a legislative showcase without transformative power because it is trapped in a political dynamic that is permissive towards corruption. Instruments such as the Corruption Law, PP 53/2010, and the code of ethics for public officials are more symbolic than substantive, thus failing to change bureaucratic behavior that is still shaped by a culture of patronage and clientelism. In contrast, Singapore proves that simple but sharp regulations, such as the Prevention of Corruption Act, when supported by an independent anti-corruption agency (CPIB), indiscriminate law enforcement, and integrity-based bureaucratic incentives, can suppress corruption to a minimum level. However, Singapore's system remains subject to criticism, particularly regarding the risk of legal authoritarianism and vulnerability to cross-border global financial issues. Therefore, this study confirms that the effectiveness of corruption eradication is not determined by the number of regulations, but rather by political consistency, independent institutional design, and the internalization of integrity values within the bureaucratic culture. For Indonesia, an important lesson from Singapore is the urgency of simplifying regulations, strengthening the independence of anti-corruption institutions, and fostering a bureaucratic culture that rejects patronage. Keywords: complexity, nurative, legislative showcase, authoritarianism, internalization, bureaucracy Abstrak: Penelitian ini menelaah kompleksitas kebijakan pengaturan konflik kepentingan dan tindak pidana korupsi antara Indonesia dan Singapura melalui pendekatan yuridis normatif. Kajian dilakukan dengan menelaah kerangka regulasi, kelembagaan, serta implementasi hukum dalam mencegah praktik penyalahgunaan jabatan publik. Hasil Penelitian menunjukkan bahwa kerangka regulasi Indonesia, meskipun komprehensif, cenderung berfungsi sebagai legislative showcase tanpa daya transformasi karena terjebak dalam dinamika politik yang permisif terhadap korupsi. Instrumen seperti UU Tipikor, PP 53/2010, maupun kode etik pejabat publik lebih bersifat simbolik daripada substantif, sehingga gagal mengubah perilaku birokrasi yang masih dibentuk oleh budaya patronase dan clientelism. Sebaliknya, Singapura membuktikan bahwa regulasi yang sederhana namun tajam, seperti Prevention of Corruption Act. Jika ditopang lembaga antikorupsi independen (CPIB), penegakan hukum tanpa pandang bulu, dan insentif birokrasi berbasis integritas, mampu menekan korupsi hingga level minimal. Meski demikian, sistem Singapura tetap menyisakan kritik, terutama terkait risiko otoritarianisme hukum dan kerentanan terhadap isu keuangan global lintas batas. Dengan demikian, penelitian ini menegaskan bahwa efektivitas pemberantasan korupsi tidak ditentukan oleh banyaknya regulasi, melainkan oleh konsistensi politik, desain kelembagaan yang independen, serta internalisasi nilai integritas dalam budaya birokrasi. Bagi Indonesia, pelajaran penting dari Singapura adalah urgensi menyederhanakan regulasi, memperkuat independensi lembaga antikorupsi, dan menumbuhkan budaya birokrasi yang menolak patronase. Kata kunci: kompleksitas, nuratif, legislatif showcase, otoritarisme, internalisasi, birokrasi